Tracking IHL Violations Through Arms Export in the Context of the Russian Aggression Against Ukraine - Iwan-Sojka, Dominika (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The paper tracks challenges to litigating (direct and indirect) imports of military equipment to Russia and Russia’s subsequent international humanitarian law of armed conflicts (IHL) violations committed in indiscriminate attacks in Ukraine. It asks whether arms export control is capable of preventing or mitigating the results of indiscriminate attacks in Ukraine. It is assumed that IHL compliance can be complemented by preventing military equipment from being delivered to recipients when there is a risk of serious IHL violations being committed with that equipment. By comparing arms transfers from Iran with other controversial arms exports, the paper examines if increased protection for IHL ensued by arms export control laws can remedy deficiencies in arms transfer decisions that do not account for IHL. If an answer is negative, corporate due diligence will perform a complementary role in respecting IHL when state authorisation for arms transfer fails to account for IHL.